Gastric volvulus is a rare and life-threatening abdominal pain - Martínez Zarazúa, Raúl Omar; Miranda, Hector Vergara; Resendez, Rafael Sáenz; Benavides, Cesar Adrián Sepulveda; Martínez, Daniel Eduardo Saldívar (International Surgery Journal, 2021)
Gastric volvulus is a rare and life-threatening abdominal pain condition resulting from the stomach twisting on its own longitudinal (organo-axial) or transverse (mesentero-axial) axis. Gastric volvulus can be primary or secondary. Secondary is most commonly related to para-esophageal hernia. Gastric volvulus can have an acute or chronic presentation, the acute form presents abdominal pain with a risk of gastric ischemia with subsequent perforation. Diagnosis is made by imaging studies such as barium contrast studies in the upper digestive tract or abdominal and chest computed tomography (CT). CT of the abdomen and thorax is very useful in the diagnosis as it can demonstrate the abnormal position and gastric torsion The goal in the definitive treatment of gastric volvulus is resolution of gastric obstruction and prevention of recurrence. Performing volvulus reduction, repair of the concomitant cause (para-esophageal hernia), fundoplication and/or gastropexy to the anterior abdominal wall. Gastropexy is considered safe and effective in elderly patients with high surgical risk.